2018
DOI: 10.1158/1538-7445.sabcs17-pd8-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD8-03: ESR1 gene fusions drive endocrine therapy resistance and metastasis in breast cancer

Abstract: Background. Dysregulation of the estrogen receptor gene (ESR1) is an established mechanism of inducing endocrine therapy resistance. We previously discovered a chromosomal translocation event generating an estrogen receptor gene fused in-frame to C-terminal sequences of YAP1 (ESR1-YAP1) that contributed to endocrine therapy resistance in estrogen receptor positive (ER+) breast cancer models. This study compares functional, transcriptional, and pharmacological properties of additional ESR1 gene fusion events of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…confirmed that expression of TNFα, IL-1β, CASP3, and CASP9 in burn injury rat models is changed [ 36 , 37 ]. Amyloid beta (A4) precursor protein, coagulation factor II (thrombin), and estrogen receptor 1 are involved mostly in Alzheimer disease, blood coagulation, and reproduction [ 38 - 40 ]. However, they are also involved in cancer and other diseases that are related to the mentioned genes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…confirmed that expression of TNFα, IL-1β, CASP3, and CASP9 in burn injury rat models is changed [ 36 , 37 ]. Amyloid beta (A4) precursor protein, coagulation factor II (thrombin), and estrogen receptor 1 are involved mostly in Alzheimer disease, blood coagulation, and reproduction [ 38 - 40 ]. However, they are also involved in cancer and other diseases that are related to the mentioned genes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid beta (A4) precursor protein, coagulation factor II (thrombin), and estrogen receptor 1 are involved mostly in Alzheimer disease, blood coagulation, and reproduction [ 38 - 40 ]. However, they are also involved in cancer and other diseases that are related to the mentioned genes [ 40 ]. The findings of Figure-3 and Table-3 are confirmed by the pathways related to the central nodes that are discussed here.…”
Section: Discussionmentioning
confidence: 99%